ONLINE GAME AS A MEDIA TO IMPROVE STUDENTS’ SPEAKING SKILL - Susi Darihastining; Imro’atus Sholihah; Faiza Nur Amalia Putri; Angga Wahyu Hidayah (Jurusan Sastra Indonesia, 2019)
College students are demanded to master a good speaking skills. This paper aims at analysing online game as a media of communicating and learning channel of students’ speaking skill. The research questions (1) Why do online game use as media in students’ speaking skill? (2) How the implementation of online game as media in students’ speaking skill. It took students from batch 2018 as the subject. This research analyzed speaking skill factors (internal and external factors), the benefit of online game on students’ speaking skills, the aspects of speaking skills which consist of language aspect (articualtion, intonation, stress, and diction) and non-langauge aspect (variation, fluency, suiatbility, expression, and attitude). It employed questionnaires, observation, and in-depth interview to collect the data. The results of this research shows (1) the factor of students’ speaking skill (internal and external factors) (2) the aspects of speaking skills which consist of language aspect (articualtion, intonation, stress, and diction) and non-langauge aspect (variation, fluency, suiatbility, expression, and attitude).